NeuroGrid: Using grid technology to advance neuroscience - Geddes, J; Lloyd, S; Simpson, A; Rossor, M; Fox, N; Hill, D; Hajnal, J; Lawrie, S; McIntosh, A; Johnstone, E; Wardlaw, J; Perry, D; et al. (2005)
Large - scale clinical studies in neuro-imaging are hampered by several factors including variances in acquisition techniques, quality assurance and access to remote datasets. The Neurogrid project will build on the experience of other UK e-science projects to assemble a grid infrastructure, and apply this to three exemplar areas: stroke, dementia and psychosis, to conduct collaborative neuroscience research. © 2005 IEEE.